The Theoretical Logic and Practical Pathways for Enhancing University Students’ Aesthetic Education Literacy through Local Traditional Culture - Yang, Jie (Journal of Social Science and Humanities, 2025)
This paper addresses prominent issues in current university aesthetic education: simplistic teaching methods that fail to cultivate aesthetic sensibility; underutilization of local cultural resources limiting critical aesthetic training; and constrained practical activities hindering the development of aesthetic creativity. Within the context of comprehensively strengthening aesthetic education in the new era, this study analyzes the theoretical basis and internal logic for its integration with local traditional culture, proposing a “Three-Dimensional Pathway” to enhance students’ aesthetic literacy. This pathway comprises: 1) Engaging through Emotion by constructing an aesthetic education system based on local traditional culture to refine students’ aesthetic perception; 2) Educating through Beauty by expanding related resources to elevate students’ aesthetic judgment; and 3) Transforming through Culture by developing aesthetic practices to foster students’ aesthetic creativity. The synergistic effect of these dimensions enriches pedagogical models in higher education, promoting the holistic and sustainable development of students’ aesthetic literacy.